Aplikasi Pengenalan Alutsista Berbasis Mobile Menggunakan Augmented Reality (AR) - Ridwan Dwi Sofian; Suhendro Busono; Yunianita Rahmawati (LPPM UBHINUS MALANG, 2023)
Indonesia as a sovereign state has made significant progress in increasing its capacity for defense. Since then, Indonesia has continued to work together to increase the capacity of defense equipment as the main support of the Indonesian National Army. In this strategic position, Indonesia has open sea and land borders with several neighboring countries. This makes Indonesia vulnerable to security threats resulting in national instability. This research aims to develop a Mobile-Based Defense Equipment Recognition Application using Augmented Reality (AR) which is able to recognition defense equipment models in the field of education, which is used as a means of learning media, so that people who don't know about defense equipment in AR form can find out. With the ability to scan objects in three dimensions, so that they can explore the introduction of defense equipment digitally through applications and can increase knowledge.